Muhammad Abid al-Jabiri's Contribution to Islamic Education - Yusrin, Yusrin (International Journal of Islamicate Social Studies, 2023)
long with the passage of time, the repertory of Islamic thinking evolves and changes. As a result, the notion of Islamic thinking must necessarily adapt to the times as a solution to ensure that Islamic thought does not fall behind. Muhammad Abid al-Jabiri is a Moroccan modern Islamic thinker who has also replied to the Arab nation's decadence and backwardness in science. It was done because he wished to restore logic and resuscitate long-dormant Islamic philosophy. The purpose of this study is to discover the notion of Muhammad Abid A-Jabiri's philosophy and his contribution to Islamic education. This study makes use of library research. Using the content analysis technique. The information comes from books, journals, and documents related to Muhammad Abid al-Jabiri. According to the findings of this study, bayani thinking is a way of thinking that is founded on the text of the Qur'an as well as the works of scholars. Bayani is the most basic idea of thinking in Islamic education, where an educator instills Islamic principles in students based on the Qur'an and hadith. Irfani, on the other hand, is a way of thinking based on direct experience through soul absorption. Burhani, on the other hand, is a way of thinking that is centered on rational reasoning or optimizing the intellect to gather information. An educator is merely a facilitator in Islamic education, and it is up to the students to study and comprehend an idea or occurrence that occurs.